Estimating Asphalt Binder Fatigue Resistance Using an Accelerated Test Method - Johnson, Carl M. (My University, 2010)
The main contribution of this study is the introduction of a method to quantify fatigue damage accumulation of asphalt binders using a short-duration test procedure that can be easily implemented into current practice. This was made possible by integrating results from the testing into an analysis procedure based on Viscoelastic Continuum Damage (VECD) concepts. The use of VECD analysis to characterize asphalt mixtures has been in use by researchers for a number of years, and it has been successfully applied in the field of asphalt mixtures to both monotonic and constant applied load amplitude cyclic (time sweep) tests. However, the application of these methods to asphalt binders has encountered a number of challenges. Monotonic testing of binders showed that, in some cases, the undamaged material response to loading is difficult to predict when some types of binder modification are used (e.g. polymers). The duration of time sweep tests is undefined, since it monitors the change in material properties with respect to number of loading cycles, and some high-performing binders can take many hours to show enough degradation to accurately assess their fatigue properties. These challenges in applying VECD concepts to binders have been resolved by using the Linear Amplitude Sweep (LAS) test. By selecting a specific ramping sequence of strains, and by combining the results with the results of a frequency sweep, it has been shown that estimation of the fatigue performance of asphalt binders can be correlated to mixture performance in the laboratory and to field fatigue performance. The accelerated loading scheme is found to give highly repeatable results and it takes less than 10 minutes to perform. The estimation of binder fatigue behavior was first validated against binder time sweep testing, followed by comparisons with asphalt mixture fatigue results, and finally with in-service (field) pavement fatigue performance. A subsequent draft standard procedure is provided, along with recommendations for inclusion of the LAS procedure for specification use.
Keywords: accelerated test methods; damage characterization; fatigue; binder; asphalt